Constructive validity of Croatian version of Pavlovian Temperament Survey (PTS) - Tatalović Vorkapić, Sanja; Lučev, Ivana; Tadinac, Meri (2008)
The aim of this study was to examine construct validity of Pavlovian temperament survey (PTS) by determining relationship between three Strelau´s dimensions of temperament (strength of excitation, strength of inhibition, mobility) and basic dimensions of personality that were defined by Eysenck and in 5-factor model of personality. It was expected that strength of excitation and mobility will have significant positive correlations with extraversion and negative correlations with neuroticism, while strength of inhibition will show significant negative correlations with neuroticism. First part of study was conducted on a sample of 74 female students with age average of 22. Pavlovian temperament dimensions were assessed with Croatian version of PTS (Lučev, Tadinac-Babić & Tatalović, 2002) and five basic dimensions of personality were measured by Five-Factor Nonverbal Personality Questionnaire, FF-NPQ (Paunonen, Ashton & Johnston, 2001). Second part of study included sample of 54 female students of psychology, with age average of 20, who completed PTS and EPQ R/A which measures dimensions of personality developed by Eysenck (Eysenck & Eysenck, 1994). Reliability coefficients for all three instruments used in this study were satisfactory but not very high. Coefficients of correlation determined in the first study were mostly not in agreement with what could be theoretically expected and empirical results of other authors, probably due to low reliability and unclear factor structure of FF-NPQ. However, results of the second study confirmed expected pattern of correlations: rSE&E=.41, p<.01, rMO&E=.65, p<.01, rSE&N=-.67, p<.01, rMO&N=-.56, p<.01 and rSI&N=-.36, p<.01, and this can be considered an indicator of good construct validity of PTS.
Projekt MZOS
ENG